Substitution of Shrimp Head Flour and Maggot Flour (Hermetia illucens) on Digestibility of Giant Shrimp (Macrobrachium rosenbergii) (Agrikan Jurnal Agribisnis Perikanan, 2022)
The research was carried out from April to December 2022 at the Integrated Laboratory at Khairun University. The research design consisted of 4 treatments that were tried, namely: Treatment A: Prawns were given 25% maggot flour + 25% prawn head flour, Treatment B: Prawns were given 20% maggot flour + 30% prawn head flour, Treatment C: Prawns were given 30% maggot flour + 20% shrimp head meal and Treatment D: Giant prawns were fed commercial feed (control). The research variables consisted of feed proximate test, feces test to determine feed digestibility of giant prawns, specific growth rate (LPS), absolute weight growth and survival rate. Based on the results of the feed proximate test showed that treatment D gave the best results by looking at the average feed protein content of 32.51%, the digestibility value was directly proportional to the feed protein value content in treatment D of 23.06%. The specific growth rate (LPS) during maintenance showed that treatment D gave the best treatment with an average growth yield of 0.684%, the best absolute growth was in treatment D with an average value of 0.120 gr. Based on the results of this study it can be concluded that the results of the proximate test of the feed showed that treatment D gave the best results as seen from the average feed protein content of 32.51%, while the digestibility value was directly proportional to the feed protein content in treatment D with an average of 23, 06%.
Keywords: Tepung kepala udang dan tepung; maggot; kecernaan; udang galah; Macrobrachium rosenbergii